Is it possible to sanitize athletes' shoes? - Messina, G.; Burgassi, S.; Russo, C.; Ceriale, E.; Quercioli, C.; Meniconi, C. (Journal of Athletic Training, 2015)
Context: Footwear should be designed to avoid trauma and injury to the skin of the feet that can favor bacterial and fungal infections. Procedures and substances for sanitizing the interior of shoes are uncommon but are important aspects of primary prevention against foot infections and unpleasant odor.